Comparison of External Beam Radiation Therapy Modalities for Hepatocellular Carcinoma With Macrovascular Invasion: A Meta-Analysis and Systematic Review - Wu, Guanheng; Huang, Guomin; Huang, Jianwen; Lu, Ligong; Peng, Shaojun; Li, Yong; Zhao, Wei (Frontiers in Oncology, 2022)
Purpose We performed a systematic review and meta-analysis to compare external beam radiation therapy modalities for hepatocellular carcinoma (HCC) with macrovascular invasion (MVI). Methods Studies were selected from online databases from the date of inception to November 2021. The outcomes of interest were overall survival (OS), objective response rate (ORR), and local control rate (LCR). Results Forty-four studies (n = 3730) were selected from 1050 articles. The pooled 1-year OS were 60.9%, 45.3%, and 44.9 for particle radiotherapy (PRT) group, conventional radiotherapy (CRT), and stereotactic body radiotherapy (SBRT) group, respectively; p = 0.005 and 0.002 for PRT vs. CRT and SBRT, respectively. Both the PRT group and the SBRT group have the advantage over the CRT group in the pooled ORR. The PRT group showed significantly higher than the CRT group (p = 0.007) in LCR. For combination therapy, CRT plus transarterial chemoembolization can prolong survival than CRT alone (p = 0.006 for 1-year OS; p = 0.014 for 2-year OS). Among grade ≥ 3 complications, the most frequent type of toxicity in CRT, SBRT, PRT group was hematological toxicity, hepatotoxicity, dermatological toxicity, respectively. Conclusions Among patients with HCC with MVI, the 1-year OS and the 2-year OS were both higher in the PRT group than in the CRT, SBRT groups. The ORR was similar between the PRT and SBRT groups. The combination therapy based on radiotherapy is expectable. PRT is associated with less complications than photon radiotherapy.